Determinants of herding behaviour on financial decisions: a theory of planned behaviour - Che Mohd Salleh, Marhanum; Mohd Nasarudin, Ahmad Fawwaz; Chowdhury, Mohammad Abdul Matin (World Academy of Islamic Management (WAIM), 2022)
This study analyses factors that influence herding behaviour among university lecturers in Malaysia. The quantitative approach is adopted through questionnaires and the theory of Planned Behaviour is chosen to identify the significant factors that influence individuals’ herding behaviour in making a financial decision with the sample of 125 university lecturers. The data were analysed using multiple regression analysis. Overall, attitude and behavioural control are found to have a significant influence towards individuals’ herding behaviour. The findings from this study indicate the unfavourable attitude towards herding behaviour among lecturers which lessens the possibility of engagement of individuals in financially related herding activities. Hence, behavioural control is found significantly influence the individuals’ herding behaviour. The findings elucidate the positive impact of behavioural control towards any individual’s financial decision including herding. It indicates that financial institutions that have strong marketing approaches and skills may influence individuals’ financial decision-making.